Pengaruh Sosial Media Dikalangan Anak dan Remaja - Wulandari, Vidia; Ramadiani, Pina; Yunita, Endah; Harahap, Riska Aprilia (YASIN, 2023)
In today's modern era, all influences in the world have begun to change. Currently the biggest influence is the presence of social media for children and adolescents. Social media currently has a major influence on society, changing the paradigm without knowing the boundaries of space, time, distance, anytime, anywhere, and without direct communication or meeting someone face to face. Through social media, of course, it will be easier to communicate in every community. Social media also brings many new events that have an impact on the development of our lives, especially on the growth and development of children and adolescents, from negative and positive consequences. Most social media users are children and adolescents who still need monitoring in their use. However, today's social media also has positive and negative influences for children and adolescents. In addition, social media also has a pretty good impact on the community. In fact, even at a young age, you can already use social media or something like that.